Il romanzo veneziano e la tradizione musicale italiana - Oliva, Gianni (Archivio d’Annunzio, 2015)
If the Fuoco is usually interpreted as the Wagnerian novel par excellence, it does not have to be underestimated the support that d’Annunzio gives the Italian music, especially the tradition that comes from Palestrina to Benedetto Marcello and to the divine Claudio Monteverdi, whose name, linked to the Lamento di Arianna, generates a devotional respect among the guests of Foscarina’s house. The exploration of d'Annunzio's wide musical culture is not original but finds its sources in the Histoire de l'Opera en Europe by Romain Rolland, already reported by Guy Tosi and now investigated with original results.